Influence of gas composition on reactive species generation in plasma-activated saline using two-stage plasma reactors system - Neto, Nilton F Azevedo; Miranda, Felipe S [UNESP]; Moreira, Pedro W P; Pessoa, Rodrigo S (IOP Publishing, 2025)
This study investigates the influence of gas composition on the generation of reactive oxygen, nitrogen, and chlorine species (RONS and RCS) in plasma-activated saline (PAS), using a sequential plasma configuration in which a dielectric barrier discharge (DBD) is coupled to a gliding arc plasma jet (GAPJ). In this setup, the gas is first treated in the DBD reactor and subsequently directed into the GAPJ, enabling successive excitation processes that enhance the production of chemically active species. Three discharge gases—pure argon, compressed air, and a 1:1 argon–air mixture—were tested to assess their impact on plasma behavior and PAS composition. Electrical and optical emission analyses demonstrated that compressed air favored NOγ and N2 emissions, while suppressing OH formation, whereas argon-rich conditions enhanced OH emission and H2O2 generation. Quantitative results showed that PAS produced with compressed air contained the highest concentrations of nitrite (20–40 mg l−1), nitrate (100–250 mg l−1), and free chlorine (1.51 mg l−1), while PAS treated with argon exhibited the highest H2O2 levels (2.0–5.0 mg l−1). Time-resolved UV–vis spectroscopy revealed progressive RONS accumulation over a 10-minute activation period, with broader absorption bands observed for air and mixed-gas treatments. Raman spectroscopy showed that vibrational modes of water were affected by the gas type, particularly in PAS treated with compressed air. These findings confirm that sequential DBD–GAPJ activation enables tunable PAS composition based on gas feed, allowing for targeted formulations with optimized oxidative profiles for antimicrobial applications, wound healing, and cancer therapy in plasma medicine.